SOCIAL PROGRESS AND ECONOMIC PROJECTS FOR DISADVANTAGED GROUPS IN ROMANIA - BALUTA, Aurelian Virgil (Annals of Spiru Haret University. Economic Series, 2016)
The paper aims to analyse the social progress, social politics, social law and successful projects applicable to the some disadvantaged groups: Roma people and woman. Inclusion of Roma people is analysed from economic point of view. The economic problems of equality by gender is presented in terms of labour rate and other relevant ratio. For Roma people the focus of analyse is also on labour involvement. The chapters of the communication are: introduction, literature review ( state of art ) in the field of social progress, theoretical background, tools for social progress in EU, economic inclusion of Roma population, economic equality by gender, conclusions.